2019
DOI: 10.18203/2349-3291.ijcp20190228
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypomagnesemia in children admitted to pediatric intensive care unit and its correlation with patient outcome

Abstract: Background: Magnesium deficiency is common in critical illness and is said to be associated with increased need for mechanical ventilation, mortality and prolonged ICU stay. The knowledge of hypomagnesemia is essential as available data is scarce and it could have prognostic and therapeutic implications. This study was undertaken to estimate the prevalence of hypomagnesemia at the time of admission in PICU and its correlation with length of PICU stay, duration on mechanical ventilator and outcome at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…63.7% with male to female ratio of 1.75:1. In the study conducted by Dandinavar et al 14 there were 56.6% males whereas there were 62% males in the study conducted by Fatima et al 16 These results were similar to ours possibly because more male children were brought for management.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…63.7% with male to female ratio of 1.75:1. In the study conducted by Dandinavar et al 14 there were 56.6% males whereas there were 62% males in the study conducted by Fatima et al 16 These results were similar to ours possibly because more male children were brought for management.…”
Section: Discussionsupporting
confidence: 84%
“…13 Regular intake of legumes, nuts, bananas and whole grains can prevent magnesium deficiency. 14 A wide variety of clinical conditions such as PEM, malabsorption, hypoalbuminaemia, sepsis, hypothermia, etc which are very common among children in developing countries are also a cause of low magnesium level. 14 Magnesium acts as a bronchodilator and also has antiinflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Dandinavar et al, in their study, have concluded that child patients with hypomagnesemia had an increased duration of PICU stay and a higher mortality rate. 13 The study's limitation was that it is a single institution study, and the sample size isn't effective in formulating a consensus. The inclusion of critically ill patients could also have helped to broaden the understanding of the importance of hypomagnesemia in critical care settings.…”
Section: Figure 2 Distribution Of Male and Female Hypomagnesemics Acmentioning
confidence: 99%
“…Nhóm bệnh tim mạch (5,8%) và chấn thương (1,2%) hiếm gặp hơn. Nghiên cứu của Dandinavar (2019) cũng ghi nhận bệnh thần kinh (36,4%) và bệnh hô hấp (26,8%) là 2 nhóm bệnh nhiều nhất ở bệnh nhi nặng điều trị tại khoa hồi sức[4]. Nghiên cứu của Erdogan (2018) ghi nhận các nhóm bệnh này với tỷ lệ khá tương tự: bệnh hô hấp 20,9%, bệnh thần kinh 20,3%, bệnh tim mạch 18,9%, nhiễm trùng huyết 10,8%[5].…”
unclassified